Superresolution mapping of energy landscape for single charge carriers in plastic semiconductors - Yifei Jiang (Nature Portfolio, 2018)
To understand the complex nanoscale structure-property relationships in conjugated polymers for device applications, new methods for tracking charge transport are required. Here, the authors employ superresolution mapping to study the charge carrier dynamics in conjugated polymer nanoparticles.